Copper Recovery from Waste Printed Circuit Board - Tran, Duc Huy; Duong, Ngoc Binh; Le, Minh Hai (Old Journal, 2018)
Electronic wasted is an important resource of secondary metals, especially copper with copper content in the wasted being up to 27%. In this work, copper was recovered from wasted printed circuit boards, a major component in any wasted electronic device. The recovery process consists of four basic steps: pre-treatment (disassembly of electronic components, abrasion and magnetic separation), roasting, smelting and anodized casting and finally electrolytic refining. After being roasted at 750°C for 45 minutes, the metal sample had a copper content of approximately 68%. The smelting and electrolytic refining process increased the purity of copper to 99.9%. The current density and Cu concentrations in the electrolyte solution are the major factors that affect the properties of the electrolytic copper.